THE INFLUENCE OF LAVENDER AROMATHERAPY TO REDUCTION MOTHER’S ANXIETY PRE OPERATION SECTIO CAESAREA IN PARADISE MATERNITY HOSPITAL KECAMATAN SIMPANG EMPAT BATULICIN 2017 - Dewi Ratna Dila; Farhandika Putra; Rani Fitriani Arifin (CNJ: Caring Nursing Journal, 2017)
The aim of this study to determine the influence of aerobic exercisethe incidence of lavender aromatherapy to reduction mother’s anxiety pre operation sectio caesarea.. This study was quasi experimental method with pre and post test without control design. The sample in this study were 20 people is mother first caesarea surgery with a purposive sampling technique. The result of this study was wilcoxon signed rank test there are difference in pretest value of pre mother’s anxiety pre operation sectio caesarea as 20 (100%) respondent and posttest value of mother’s anxiety pre operation sectio caesarea as 16 (80%) respondent, indicated that the p value of 0,000 (< 0.05). The conclusion of this study there was the influence was influence of lavender aromatherapy to reduction mother’s anxiety pre operation sectio caesarea. in Paradise Maternity Hospital Kecamatan Simpang Empat Batulicin 2017. It is recommended that giving aromatherapy lavender can be used as an alternative to lower anxiety levels in patients before surgery sectio caesarea and for subsequent researchers to continue and develop existing research.